Protocol for Short- and Longer-term Spatial Learning and Memory in Mice - Willis, Emily F.; Bartlett, Perry F.; Vukovic, Jana (Frontiers in Behavioral Neuroscience, 2017)
Studies on the role of the hippocampus in higher cognitive functions such as spatial learning and memory in rodents are reliant upon robust and objective behavioral tests. This protocol describes one such test — the active place avoidance task. This behavioral task involves the mouse continuously integrating visual cues to orientate itself within a rotating arena in order to actively avoid a shock zone, the location of which remains constant relative to the room. This protocol details the step-by-step procedures for a novel paradigm of the hippocampal-dependent active place avoidance task, measuring acquisition of spatial learning during a single 20-min trial (i.e. short-term memory), with spatial memory encoding and retrieval (i.e. long-term memory) assessed by trials conducted over consecutive days. Using the active place avoidance task, cognitive flexibility can be assessed using the reversal learning paradigm, as this increases the cognitive load required for efficient performance in the task. In addition to a detailed experimental protocol, this paper also describes the range of its possible applications, the expected key results, as well as the analytical methods to assess the data, and the pitfalls/troubleshooting measures. The protocol described herein is highly robust and produces replicable results, thus presenting an important paradigm that enables the assessment of subtle short-term changes in spatial learning and memory, such as those observed for many experimental interventions.